THE UTILIZATION OF DIGITAL MEDIA IN HEALTH COMMUNICATION IN INDONESIA - Moehammad Iqbal Sultan; Andi Subhan Amir (Jurnal Riset Komunikasi, 2023)
The digital era has brought many changes in various aspects of life, including the health sector. Digital media is a health communication tool to disseminate information, education, and knowledge about health. Digital media plays an essential role in changing how people get and understand health information. This research article describes the use of digital media in health communication in Indonesia and how it has changed the traditional paradigm of delivering health information. A qualitative approach through literature review and in-depth interviews with stakeholders using digital media for health communication in Indonesia. These stakeholders include health practitioners, health app developers, digital health service users, and health communication experts. This article shows how digital media, such as websites, mobile apps, and social media, have improved people's health knowledge and behavior. The findings show that digital media have become important health information channels, facilitating interactions between healthcare providers and the public. However, challenges related to information reliability and digital literacy are of concern. Therefore, this study emphasizes the importance of ongoing efforts to improve digital literacy and ensure the reliability of health information disseminated through digital media.